Transformational Leadership and Turnover Intentions among School Teachers in the Deep South of Thailand - Promchart, Krisana; Potipiroon, Wisanupong (The Journal of Behavioral Science, 2020)
School teachers in the deep south of Thailand have been affected by the violence and unrest that have plagued this region for almost two decades. It has been reported that hundreds of school teachers have left their jobs and moved out of the affected areas. This research uses the insights from behavioral research (e.g. need theories) to propose that transformational school leaders can play a crucial role in reducing teachers’ turnover intentions by altering their safety perceptions and job satisfaction. In particular, this study takes a multilevel perspective to test this hypothesis, both at the individual and organizational levels of analysis. Based on the data obtained from 779 teachers in 82 primary schools located in the three southernmost provinces of Thailand, multilevel structural equation modeling analysis was used for testing the proposed theoretical model. Specifically, at both the individual and organizational levels of analysis, the results indicated that the relationship between transformational leadership and turnover intentions was fully and sequentially mediated by perceived safety and job satisfaction (individual-level indirect effect index: -0.02; SE = 0.01; 90% CI [-0.03, -0.01]; organizational-level indirect effect index: -0.13; SE = 0.07; 90% CI [-0.25, -0.01]). These findings suggest that transformational leaders can play a special role in reducing employee anxiety in uncertain contexts. This research also contributes to behavioral science research by proposing the mediating role of perceived safety in the relationship between transformational leaders and employee turnover intentions. Several theoretical and practical implications emerged from the present findings.